Aesthetic hybridity of the song “Jali-jali” in Gambang Kromong music - Yusuf Arrahman; Ni Wayan Ardini; I Komang Sudirga (Journal of Aesthetics, Creativity and Art Management, 2022)
"Jali-jali" in Gambang Kromong (Kromong Xylophone) music is a very popular Betawi song. This song is the result of acculturation of Betawi and Chinese culture. The popularity of “Jali-jali” is inversely proportional to the existing literature about this song. This study aimed to understand its specificity thoroughly. It is a type of field research by describing the data qualitatively and the selection of theory is based on data in the field. The type of data in this study is qualitative data. Research data sources consist of primary and secondary data sources. Data were collected through interview, observation, documentation and literature studies. Data analysis was carried out by data reduction, data presentation, and data verification. The results show that in "Jali-jali" the hybridity of Chinese and Betawi culture can be seen from the cultural aspects, namely ideas, activities, and artifacts. There is also a musical aspect in the playing of Tehyan which has a diatonic scale and Gambang Kromong which has a pentatonic scale. The form of "Jali-jali" in Gambang Kromong music is A-B-A-B-C, has 10 sentences and 5 periods. The aesthetics of "Jali-jali" is found in the melodic tone that sounds distinctive because the differences in the hybridity of Betawi music and Chinese music produce a contrasting melody, from which there is a very distinctive harmonization so that "Jali-jali" in Gambang Kromong music is closely related to Betawi cultural identity.